Analisis Asas Keseimbangan Dalam Syarat Dan Ketentuan Layanan PT Commerce Finance Bagi Penerima Pinjaman - Salwa Salsabila Wibawa; Arief Suryono (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is a normative legal research with a statutory approach. Shopee Paylater is a method of paying for an item in installments, where people can buy goods now and make payments at a later date in installments for 1, 3, 6, 12, 18, or 24 months on a predetermined due date. This research was conducted to determine the application of the principle of balance in Shopee paylater for loan recipients which is included in a standard agreement and is prone to violating the provisions in the applicable regulations. The result of this research is that the terms and conditions of Shopee paylater for loan recipients have not applied the principle of balance.